PTFE-modified porous surface: Eliminating boiling hysteresis. (February 2020) - Wang, Ya-Qiao; Luo, Jia-Li; Heng, Yi; Mo, Dong-Chuan; Lyu, Shu-Shen
Abstract: Boiling hysteresis is a side effect that usually occurs with overshot temperature before steady boiling, often noted as a start-up problem. This phenomenon tends to emerge when porous surfaces are used to enhance boiling heat transfer performance. It is important to reduce or eliminate hysteresis before various micro−/nanoporous surfaces can be deemed acceptable in the thermal management industry. In this study, a two-layer composite surface (TLCS) with a copper forest structure at the bottom and micro-nano biporous structure at the top showed good enhancement at a heat transfer coefficient of 340% and critical heat flux of 67% compared to a plain copper surface with water as the working fluid at atmosphere. However, boiling hysteresis occurred on TLCS; the highest wall superheat temperature difference between steady boiling and the start-up process was approximately 13.5 K at 140 W cm −2 . When TLCS was modified with Polytetrafluoroethylene (PTFE), the temperature difference at the same heat flux was less than 0.5 K, demonstrating that the boiling hysteresis phenomenon was successfully eliminated.